Insights in the Application of Stoichiometric and Non-Stoichiometric Titanium Oxides for the Design of Sensors for the Determination of Gases and VOCs (TiO2−x and TinO2n−1 vs. TiO2) - Simonas Ramanavicius (Sensors, 2020)
In this review article, attention is paid towards the formation of various nanostructured stoichiometric titanium dioxide (TiO2), non-stoichiometric titanium oxide (TiO2−x) and Magnéli phase (TinO2n−1)-based layers, which are suitable for the application in gas and volatile organic compound (VOC) sensors. Some aspects related to variation of sensitivity and selectivity of titanium oxide-based sensors are critically overviewed and discussed. The most promising titanium oxide-based hetero- and nano-structures are outlined. Recent research and many recently available reviews on TiO2-based sensors and some TiO2 synthesis methods are discussed. Some promising directions for the development of TiO2-based sensors, especially those that are capable to operate at relatively low temperatures, are outlined. The applicability of non-stoichiometric titanium oxides in the development of gas and VOC sensors is foreseen and transitions between various titanium oxide states are discussed. The presence of non-stoichiometric titanium oxide and Magnéli phase (TinO2n−1)-based layers in ‘self-heating’ sensors is predicted, and the advantages and limitations of ‘self-heating’ gas and VOC sensors, based on TiO2 and TiO2−x/TiO2 heterostructures, are discussed.